Empresas de inovação social: visões de mundo de fundadores e práticas organizacionais - Simões, Luis Francisco Marques (2016)
Although several companies have experienced greater economic and social development in the last century, social problems persist in areas such as health, education, housing and environmental management. This situation led actors of society to seek innovative solutions to mobilize social and economic forces, for a better world, balanced and fair. In this sense, we see the role of social innovation entrepreneurs who is sensitive to local challenges, know that it is not sustainable to past success patterns. Social innovations create solutions from the public itself needs who wish to attend, by the active participation of the various stakeholders involved, ensuring the sharing of solutions proposed for other communities. The need for capital, however, is one of the critical aspects for the implementation and maintenance of organizations that generate this kind of innovation, which has opened space for funds philanthropic venture capital act as stakeholders in for-profit organizations geared to social innovation. Since these companies are challenged to meet social and economic objectives, counting, often with the presence of investors in their management, this research sought to understand how social innovation entrepreneurs deal with the tension between organizational goals antagonistic by the investigation of the business world views that have and its reflection in organizational practices they have identified. To achieve the proposed objective, there was a basic interpretive qualitative research, using, fundamentally, semi-structured and in-depth interviews, covering six founding of social innovation companies, which were analyzed by interpretative textual analysis with categorization a priori and a posteriori. The results allowed to establish relations between the life story of social entrepreneur and social innovation company, two views of the business world “actually is “ and “how it should be”, present in the founders. The presence of these business worldviews contributed to the decision of founding of social innovation companies as an alternative form of enterprise, within the capitalist context of private organizations and practices implemented to integrate the objectives, social and economic, which are them inherent.